Clinical pharmacology of the combination of ACE inhibitors and calcium antagonists: benefits of the perindopril arginine and amlodipine combination - M. V. Leonova (Кардиоваскулярная терапия и профилактика)
The paper reviews the modern evidence on mechanisms of action and clinical effectiveness of two cardiovascular medication classes – angiotensin-converting enzyme (ACE) inhibitors and calcium antagonists (CA), used for the treatment of patients with arterial hypertension (AH) and coronary heart disease (CHD). ACE inhibitors and CA have complementary effects on vascular tone and endothelial function, as well as synergetic action in terms of blood pressure (BP) reduction, pleiotropic effects, organo-protection, and clinical event prevention. Therefore, these mediations can be used as combined cardiovascular therapy. Perindopril and amlodipine, both as monotherapy or combined treatment, have the largest evidence base and potential for clinical practice.